2022
DOI: 10.1155/2022/2219006
|View full text |Cite
|
Sign up to set email alerts
|

BSPPF: Blockchain‐Based Security and Privacy Preventing Framework for Data Middle Platform in the Era of IR 4.0

Abstract: Security and privacy issues about Big Data have emerged as one of the most pressing concerns in both academic circles and the business world in the era of IR 4.0. These worries are made worse because businesses are beginning to construct their own Big Data-based Data Middle Platform. The research team has summarized the security and privacy protection issues of Big Data-based Data Middle Platform by combining previous research and providing a table that lists some contributions that the blockchain uses for sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Blockchain development involves the creation, implementation, and maintenance of decentralized, distributed ledger systems. There are four stages of Blockchain development: Blockchain 1.0, Blockchain 2.0, Blockchain 3.0, and Blockchain 4.0 40,41 . Hameed et al 42 revealed that Blockchain 5.0 is currently in development, with researchers actively striving to enhance its functionality across various business models.…”
Section: Blockchain Endpoint and Taxonomymentioning
confidence: 99%
“…Blockchain development involves the creation, implementation, and maintenance of decentralized, distributed ledger systems. There are four stages of Blockchain development: Blockchain 1.0, Blockchain 2.0, Blockchain 3.0, and Blockchain 4.0 40,41 . Hameed et al 42 revealed that Blockchain 5.0 is currently in development, with researchers actively striving to enhance its functionality across various business models.…”
Section: Blockchain Endpoint and Taxonomymentioning
confidence: 99%